Persistence-based clustering with outlier-removing filtration - Bois, Alexandre; Tervil, Brian; Oudre, Laurent (Frontiers in Applied Mathematics and Statistics, 2024)
This article describes a non-parametric clustering algorithm with an outlier removal step. Our method is based on tools from topological data analysis: we define a new filtration on metric spaces which is a variant of the Vietoris–Rips filtration that adds information about the points' nearest neighbor to the persistence diagram. We prove a stability theorem for this filtration, and evaluate our method on point cloud and graph datasets, showing that it can compete with state-of-the-art methods while being non-parametric.